Awareness of food nutritive value and eating practices among Nigerian bank workers: Implications for nutritional counseling and education - Eze, Ngozi M. (Medicine (Baltimore), 2017)
Adequate nutrition is an important aspect of a healthy lifestyle for all individuals, including bank staff. The objective of this study was to investigate the awareness of food nutritive value and eating practices among bank workers in Lagos State, Nigeria. The study adopted a cross-sectional descriptive survey design. A purposive sample of 250 bank workers took part in the study. Means and Student t tests were employed for data analysis. Results showed that bank workers were aware of the nutritive value of foods, and that eating practices commonly adopted included skipping breakfast, eating breakfast at work, buying food at work from the bank canteen, eating in between meals, buying snacks as lunch, and consuming soft drinks daily, among others. There were no significant differences between male and female bank workers in mean responses on food nutritive value or in eating practices adopted. Good eating habits will help bank workers not only to improve their nutritional well-being, but also to prevent nutrition-related diseases. The implications for nutritional counseling and education are discussed in the context of these findings.